Pelatihan Academic Skills Dalam Mengelola Keuangan Pada UMK Rindang Alam Kel. Koto Lua, Kec. Pauh Kota Padang - Henny Sulistianingsih; Dian Hirma; Maivalinda Maivalinda; Rita Srihasnita RC; Lasti Yossi Hastini (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
This service aims to realize the implementation of an academic skills training program (academic skills) in managing finances for MSEs (housewives/partners) who have businesses. These service partners are general community groups consisting of mothers who almost all have small businesses and are members of a study group called the Rindang Alam Keluharan Koto Lua Study Group, Pauh District Padang city. The training program includes training in (1) personal skills, including self-knowledge, rational thinking skills, and self-confidence, (2) social skills, (3) social skills academic skills, (4) vocational skills The training provided for this service activity focuses on the third program, namely on Academic Skills. The final output of this service is to prepare an active Rindang Alam Study Group which is trained and fostered in material about academic skills with a financial management training program. published in journals. The results of this training activity are that the Rindang Alam Study Group can understand financial terms and make bookkeeping in a simple way. In addition, the impact of the implementation of this training program showed a positive impact, namely the mothers of the Rindang Alam study group could recognize their own character and competence, work independently and in groups, utilize their knowledge to gain entrepreneurial opportunities and more income.